Akibat Hukum Jual Beli di Bawah Tangan atas Tanah Hak Milik di Kabupaten Badung - I Gusti Agung Ayu Lita Pratiwi; Nella Hasibuan Oleary; Ni Made Puspasutari Ujianti (Warmadewa Press, 2020)
The sale and purchase transaction in Badung Regency which was made by both parties was in the form of an agreement of hands, but one of the parties who broke a promise or could be called a default. The purpose of this research is to see the legal dangers of underhand trading on land ownership in Badung Regency. This research method uses empirical legal research. In practice, the implementation of binding purchases and purchases under land ownership rights is often carried out by several parties, one of which occurred in Badung Regency. The practice of buying and selling land carried out under the hand is not in accordance with government regulation Number 24 of 1997 concerning Land Registration, which requires that the sale and purchase be made with an authentic deed, and not under hand. However, the buying and selling process in Lukluk District, Mengwi District, Badung Regency is still ready for those who, the deed, because the fulfillment of the legal requirements for buying and selling under the UUPA is material, formal and cash, clear and sincere. In principle, in fine sales agreements and notaries will be a legal approach as law for them made. And also according to article 1320 of the Civil Code the validity of an agreement if, among others: There is an agreement, skills, certain matters, and valid reasons. And although according to lawful compliance with the requirements according to article 1320 of the Civil Code, the sale and purchase of land must be carried out before the prohibited authority (PPAT).